Evaluation on New Natural Coagulant Aid in Water Treatment and its Life Cycle Assessment - Lau, Jia Shen (Universiti Teknologi PETRONAS, 2020)
Coagulation-flocculation is the key conventional process water turbidity reduction in water treatment plant. However, various shortcoming has been identified through the usage of inorganic coagulant such as aluminium sulphate in coagulation-flocculation process where it possesses threat on both human health and environment. Hence, natural coagulant as an alternative for the coagulation-flocculation process has become a field of interest in providing clean water for the community. In this research, mucilage extracted from rocket seed as natural coagulant aid is studied for the removal of water turbidity. The potential coagulant aid is combined with the utilisation of Fe3+ coagulant in the coagulation-flocculation process for treating surface water.